Comparison of Effect of Antidepressants on Psychomotor Functions - Mendhe, Pranjali P. (Indian J Psychol Med, 2017)
OBJECTIVE: The comparison of the effect of antidepressants on psychomotor functions in patients with endogenous depression. MATERIALS AND METHODS: This prospective interventional study was carried out at a tertiary care teaching hospital on 95 literate patients with newly diagnosed endogenous depression matching inclusion and exclusion criteria. Patients were prescribed either desvenlafaxine (50 mg) or fluoxetine (40 mg) or sertraline (50 mg). Psychomotor functions were assessed by digit letter substitution, six letter cancellation, choice reaction time, hand steadiness and flicker fusion test at the baseline 1(st) month and 3(rd) month. Efficacy of drugs was also measured by Hamilton rating scale for depression. Data were analyzed by using ANOVA and P < 0.05 was considered as statistically significant. RESULTS: A total of 95 patients were enrolled. Fluoxetine, desvenlafaxine, and sertraline were prescribed in 32, 32, and 31 patients, respectively. At the end of 3 months, a significant improvement in psychomotor functions was observed in patients treated with sertraline (P < 0.05), while desvenlafaxine-treated patients did not show any significant change in any of the tests. Surprisingly, fluoxetine-treated patients showed deterioration in all psychomotor tests (P < 0.05). Hamilton rating score improved at the end of 3 months treatment as compared to baseline. Most commonly observed adverse reactions in all three drug groups were nausea (n = 20), dizziness (n = 3), headache (n = 20), and diarrhea (n = 3). CONCLUSION: Sertraline significantly improves psychomotor function as compared to desvenlafaxine while fluoxetine impairs.